"Most of the People My Age Tend to Move Out": Young Men Talking about Place, Community, and Belonging in Manchester. Issue 2 (1st December 2019) - Badwan, Khawla; Wilkinson, Samantha
Abstract : Universities are as a means of leaving for the city for young people living increasingly precarious and mobile lives. This article explores how male university students (aged 18–25) talk about, and belong to, the places they inhabit in Greater Manchester, England. Drawing on mixed-methods data collection from survey responses and in-depth semi-structured interviews, this article finds that while young men embrace liquid understandings of place, they express tensions between "insiders" and "outsiders." While universities appear to be significant places for male university students, only half the participants reported feelings of belonging to university communities. Consequently, this article proposes recommendations for universities, in order to ensure male university students feel they can open up to staff, thereby enabling them to feel part of a "learning community"—a key theme of the National Student Survey.